Photoperiodic dependent regulation of photosynthesis in the polar diatom Fragilariopsis cylindrus - Guérin, Sébastien; Bruyant, Flavienne; Gosselin, Michel; Babin, Marcel; Lavaud, Johann (Frontiers in Photobiology, 2024)
Polar microalgae are exposed to dramatic seasonal changes in light availability, from continuous summer days to winter nights with rapid changes of the daylength in spring and fall. Under this challenging light climate, large diatoms spring blooms occur at the bottom sea-ice and underneath the icepack, accounting for a significant proportion of the annual marine primary production in the Arctic Ocean. The on-going earlier melt down of the snow and ice covers result in a stronger light penetration and consequent increase in irradiance at the bottom of the sea ice leading to earlier seasonal sea-ice diatom blooms under shorter daylengths. Therefore, elucidating the response of polar diatoms to different photoperiods will help to better understand the consequences of the changing arctic climate on their photosynthetic productivity. In this study, we characterized the response of Fragilariopsis cylindrus, a model polar diatom, across five different photoperiods with similar light and temperature conditions (30 μmol photons m -2 s -1 and 0°C respectively). We report different photoacclimative strategies under shorter and longer daylengths, with the special case of prolonged darkness (mimicking winter polar night). We also observed a repeated daily regulation of the photochemistry and photoprotection parameters when cells were exposed to a light:darkness alternation, despite the constant and optimal light intensity during the light periods. Our results highlight the ability of F. cylindrus to grow efficiently under a wide range of daylengths, finely adjusting the balance between photochemistry and photoprotection to make the best use of the available light, supporting sustained production and growth despite low light and temperature.